Ultra-wideband array antenna in 5G and its miniaturization technology - Shenke ZHANG; Fengxu YANG; Yingzeng YIN (Dianxin kexue)
The design method of wideband array antennas and the technology of low profile were studied. Combinations of commercial simulation software ADS and Ansoft HFSS, two design examples of tightly coupled array antennas were presented, with the characteristic of wideband and low profiles. Simulated results show that the impedance bandwidth of voltage stranded ratio less than 2. 0 was from the frequency range of 0.67 GHz to 3. 78 GHz, with a height of 40.25 mm. Moreover, by loaded artificial magnetic conductor (AMC) structure on the basis of the original antenna array to form a high impedance surface to improve the high-frequency resonance performance, the low profile technology was presented for wideband array. The results of full wave electromagnetic simulation software show that the impedance bandwidth of voltage stranded ratio less than 2. 0 was from the frequency range of 1. 1 GHz to 2. 8 GHz, with a height of 24 mm and corresponding to a fractional bandwidth of 78. 0%. This technology can be extended to the development of 5G antennas.